Role of Village Women in Empowerment Programs As a Development Achievement (Studies at a Women's School in Kesambenkulon Village, Kec. Wringinanom Kab. Gresik) - Sholihah, Hidayatus; Kholifah, Siti; Wike, Wike (Wacana Journal of Social and Humanity Studies, 2023)
The issue of gender is one of the main issues in current development, especially in the development of human resources. Women's empowerment is a step a group of actors takes to create more decent living conditions and obtain their rights as human beings in development. This research was conducted to determine the role of women in implementing women's empowerment programs through the Women's School. In conducting this study, the researcher used the ACTORS theory offered by Sarah Cook and Sara H. Longwe's gender analysis. The method used in this study is a descriptive qualitative approach, where in collecting data, the researcher uses in-depth interviews (interviews), observation, and documentation. The study results concluded that implementing the Women's Empowerment Program through Women's Schools followed the success indicators from the Actors theory perspective. In the view of the actor's theory, each hand is proven to increase the role of Kesambenkulon village women. The output or result of the empowerment program is also the output or result desired by the women of the Kesambenkulon village, namely in the form of increasing Self Respect, Self Confidence, and Self Reliance. Meanwhile, viewed from the gender analysis perspective of Sara H. Longwe, it shows that the women's empowerment program carried out to increase the role of village women through the Women's School in Kesambenkulon village has reached a high level, namely the Control level. Keywords: women's empowerment, ACTORS theory, longwe's analysis